Strategi Pengembangan Ekstrakurikuler Untuk Meningkatkan Kemampuan Afektif Siswa Sekolah Dasar - Mochammad Ramdan Samadi; Laesti Nurishlah; Siti Mariam (STAI Al-Mas'udiyah, 2023)
Extracurriculars play a crucial role in the development of elementary school students as they provide an additional platform for exploration, social interaction and skill development that are not covered in the academic curriculum. Through active participation in extracurricular activities, students can strengthen their affective abilities, such as empathy, independence, and self-confidence, which form the basis for their holistic development. This research explores extracurricular development strategies aimed at improving the affective abilities of elementary school students. Through a qualitative approach, this literacy study analyzes various sources to identify effective strategies. The findings highlight the importance of using play, art, and collaboration methods in designing extracurricular programs that strengthen students' affective aspects. An emphasis on developing social skills, empathy, and leadership is also highlighted. The implications of this research provide valuable insight for policy makers and educational practitioners to design holistic and effective extracurricular programs.